PENGARUH MODEL PEMBELAJARAN PERMAINAN MODISCO BALL TERHADAP KETERAMPILAN PASSING DALAM PERMAINAN SEPAKBOLA - Jaka Jaka (Journal of Physical Education and Sport Science, 2022)
The Influence of the Modisco Ball Game Learning Model on Passing Skills in Football Games" in fifth grade students of SD Negeri 2 Ancaran. The purpose of this study was to produce a soccer learning model in the form of a modisco ball game to overcome students lack of activity and interest and to form modifications according to the characteristics of fifth grade students of SD Negeri 2 Ancaran in physical education learning. This study uses a field experiment method. The population and sample of this study were the fifth grade students of SD Negeri 2 Ancaran, totaling 29 people. The results of the analysis and processing of the pre-test data obtained the lowest score of 3 and the highest score of 7. While the post-test data obtained the lowest score of 6 and the highest score of 11, the average pre-test result was 8.5 and post-test of 16.03 there is an increase of 7.53. Thus, based on the table of paired samples t-test, it is known that the value of sig (2-tailed) is 0.000. Because the value of sig ( 2-tailed ) 0.000 < 0.05 , thus is rejected and is accepted. This means that there is an increase in the passing of fifth grade students of SD Negeri 2 Ancaran in the learning of modisco ball